Pembinaan Kawasan Tanpa Rokok Pada Rumah Sakit Jiwa Tampan Provinsi Riau - Kenny Diya Putri; Zaili Rusli (PUBLIKA : Jurnal Ilmu Administrasi Publik, 2021)
This research was conducted with the aim of being able to find out and analyze how the development related to the Non-Smoking Area and the inhibiting factors in the implementation of the No Smoking Area Development at the Tampan Mental Hospital of Riau Province was carried out. Therefore, as one of the hospitals that is quite crowded by the public, the regulations regarding the Non-Smoking Area should be applied maximally in order to maintain common interests related to health. The coaching concept used is the Hidayat concept which says there are 4 forms of coaching, namely: 1) Giving Directions, 2) Providing Guidance, 3) Conducting Supervision, 4) Providing Education and Training. The type of research used is descriptive qualitative research. Data collection techniqyes using observation, interviews and documentation. The results of this study indicate that in conducting the development of a No Smoking Area at the Tampan Mental Hospital, Riau Province, it has not been said to be optimal. In carrying out the guidance, there are still obstacles that occur such as 1) Low public awareness in complying with regulations related to Non-Smoking Areas, 2) There is no special section in carrying out development related to Non-Smoking Areas at the Tampan Mental Hospital of Riau Province.